1968
DOI: 10.1111/j.1529-8817.1968.tb04681.x
|View full text |Cite
|
Sign up to set email alerts
|

PRODUCTION OF MALE GAMETES AND AUXOSPORES IN THE CENTRIC DIATOMS CYCLOTELLA MENEGHINIANA AND C. CRYPTICA12

Abstract: Vegetative cells of Cyclotella meneghiniana Kützing form male gametes and anxospores following transfer from a synthetic freshwater medium to a modified artificial seawater. Both spermatogenesis and auxospore formation are correlated with an increase in the Na(+) concentration in the medium. Spermatogenesis can also be induced in C. cryptica Reimann, Lewin, and Guillard in artificial seawater with an adjusted sodium level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…The size of the cell that differentiates into an egg has a positive correlation with the size of the fully expanded auxospore (and hence with the initial vegetative cell size) in several centric diatoms [27]. By contrast, the number of sperm produced by one cell is not affected by cell size in C. meneghiniana [12]. These observations suggest that allocation of larger cells to females more effectively restores cell size in the next vegetative cycle.…”
Section: (B) Intrinsic and Extrinsic Factors In Sex Allocation By Motmentioning
confidence: 99%
“…The size of the cell that differentiates into an egg has a positive correlation with the size of the fully expanded auxospore (and hence with the initial vegetative cell size) in several centric diatoms [27]. By contrast, the number of sperm produced by one cell is not affected by cell size in C. meneghiniana [12]. These observations suggest that allocation of larger cells to females more effectively restores cell size in the next vegetative cycle.…”
Section: (B) Intrinsic and Extrinsic Factors In Sex Allocation By Motmentioning
confidence: 99%
“…Based on her observation of large genetic variation and paraphyly of plastid RFLPs, Bourne (1992) considered that it might be a complex of several species. On the other hand, Drebes (1977) suggested that C. meneghiniana had abandoned allogamy: although sexual reproduction had been studied intensively in this species (Iyengar & Subrahmanyan, 1944;Schultz & Trainor, 1968;Rao, 1970Rao, , 1971Rao, , 1996Ha˚kansson & Chepurnov, 1999), no observations of allogamous fertilization have ever been published.…”
Section: Introductionmentioning
confidence: 95%
“…Rapid changes in environmental factors such as salinity (diatoms: Schultz & Trainor, 1968) and pH (e.g. Pediastrum duplex Meyer: Wilcox & Floyd, 1988) can induce gametogenesis.…”
Section: The Effect Of Environmental Factors Onmentioning
confidence: 99%